## f(1)=3 , f(n)= 6*f(n-1) for n ≥ 2

### In this problem, we are given a recursive formula for a function f(n), where f(1) is defined as 3 and f(n) is defined as 6 times f(n-1) for n greater than or equal to 2

In this problem, we are given a recursive formula for a function f(n), where f(1) is defined as 3 and f(n) is defined as 6 times f(n-1) for n greater than or equal to 2.

To find the value of f(n) for a given n, we can use the recursive formula to iteratively compute the results.

Let’s start by finding the value of f(2):

f(2) = 6 * f(2-1) = 6 * f(1) = 6 * 3 = 18

Next, we can find the value of f(3):

f(3) = 6 * f(3-1) = 6 * f(2) = 6 * 18 = 108

Continuing this process, we can find the values of f(4), f(5), and so on.

f(4) = 6 * f(4-1) = 6 * f(3) = 6 * 108 = 648

f(5) = 6 * f(5-1) = 6 * f(4) = 6 * 648 = 3888

We can see that the values of f(n) increase rapidly as n increases.

In general, the recursive formula f(n) = 6 * f(n-1) can be written as:

f(n) = 6^n * f(1)

Therefore, we can find the value of f(n) by multiplying 6 raised to the power of (n-1) with f(1).

To summarize:

f(1) = 3

f(n) = 6^n * f(1) for n greater than or equal to 2

##### More Answers:

Understanding the Recursive Definition of the Function f(n) and Finding Values Using the FormulaRecursive Formula for f(n) with Examples | Find f(2) and f(3) and Understand the Concept of Recursion in Mathematics

Recursive Math Function | Calculating f(n) using f(n-1) + 6